Complexes of a gallium heterocycle with transition metal dicyclopentadienyl and cyclopentadienylcarbonyl fragments, and with a dialkylmanganese compound. - Aldridge, S; Baker, R; Coombs, N; Jones, C; Rose, R; Rossin, A; Willock, D (2006)
The reactivity of several transition metal half sandwich complexes towards an anionic gallium(I) heterocyclic complex, [K(tmeda)][Ga{[N(Ar)C(H)]2}](Ar = C6H3Pri2-2,6), has been investigated. This has led to the anionic half sandwich complexes, [K(tmeda)][(C5H4R)M(CO)n[Ga{[N(Ar)C(H)]2}]](M = V, R = H, n= 3; M = Mn, R = Me, n= 2; M = Co, R = H, n= 1), which crystallographic studies show to form dimers (M = Mn and Co) or a polymer (M = V) through bridging potassium cations. The metal-gallium bond lengths in all complexes are very short which, combined with some spectroscopic evidence, is suggestive of M-Ga pi-bonding. Density functional theory studies of models of all complexes indicate that the level of back-bonding in these complexes is, however, minimal and of a similar order to that seen in analogous complexes incorporating neutral N-heterocyclic carbene ligands. Reactions of the metallocenes, [M(C5H4Me)2](M = V or Cr), with the digallane4, [Ga{[N(Ar)C(H)]2}]2, have afforded the neutral complexes, [M(C5H4Me)2[Ga{[N(Ar)C(H)]2}]], which are thought to be formed via an initial oxidative insertion of the transition metal centre into the Ga-Ga bond of the digallane. X-Ray crystallography shows the complexes to be monomeric. One (M = V) reacts with one equivalent of [K(tmeda)][Ga{[N(Ar)C(H)]2}] to give the crystallographically characterised, anionic bis(gallyl)-complex, [K(tmeda)][V(C5H4Me)2[Ga{[N(Ar)C(H)]2}]2]. For comparison, the reaction of [K(tmeda)][Ga{[N(Ar)C(H)]2}] with [Mn{CH(SiMe3)2}2] was carried out and gave the monomeric, anionic complex, [K(tmeda)][Mn{CH(SiMe3)2}2[Ga{[N(Ar)C(H)]2}]].